George Orwell and the Defence of English Food - Perkins, Blake (Petits Propos Culinaires, 2014)
The article explores George Orwell’s an abiding if eccentric interest in food. He even thought ‘it could be plausibly argued that changes in diet are more important than changes of dynasty or even of religion.’ To illustrate the point he added somewhat implausibly that the ‘Great War, for instance, could never have happened if tinned food had not been invented.’